Decellularised scaffolds: just a framework? Current knowledge and future directions. (July 2020) - García-Gareta, Elena; Abduldaiem, Yousef; Sawadkar, Prasad; Kyriakidis, Christos; Lali, Ferdinand; Greco, Karin Vicente
The use of decellularised matrices as scaffolds offers the advantage of great similarity with the tissue to be replaced. Moreover, decellularised tissues and organs can be repopulated with the patient's own cells to produce bespoke therapies. Great progress has been made in research and development of decellularised scaffolds, and more recently, these materials are being used in exciting new areas like hydrogels and bioinks. However, much effort is still needed towards preserving the original extracellular matrix composition, especially its minor components, assessing its functionality and scaling up for large tissues and organs. Emphasis should also be placed on developing new decellularisation methods and establishing minimal criteria for assessing the success of the decellularisation process. The aim of this review is to critically review the existing literature on decellularised scaffolds, especially on the preparation of these matrices, and point out areas for improvement, finishing with alternative uses of decellularised scaffolds other than tissue and organ reconstruction. Such uses include three-dimensional ex vivo platforms for idiopathic diseases and cancer modelling.